VD_FINDINFO Jug / 2015 / 355 vom 13. März 2015 - VD Tribunal cantonal (2015)
ABUS D'AUTORITÉ, LÉSION CORPORELLE, AGRESSION, DOUTE, GARDIEN DE PRISON, ACQUITTEMENT | 123 ch. 1 CP, 123 ch. 2 CP, 134 CP, 14 CP, 312 CP, 10 CPP (CH)